Correction: An anionic and cationic surfactant-assisted hydrothermal synthesis of cobalt oxide nanoparticles as the active electrode material for supercapacitors. (24th February 2021) - Samal, R. R.; Samantara, Aneeya K.; Mahalik, S.; Behera, J. N.; Dash, B.; Sanjay, K.
Abstract : Correction for 'An anionic and cationic surfactant-assisted hydrothermal synthesis of cobalt oxide nanoparticles as the active electrode material for supercapacitors' by R. R. Samal et al., New J. Chem., 2021, 45, 2795–2803; DOI: ; 10.1039/D0NJ05088A .